The Readiness of Human Resource Management for Industrial Business Sector towards Industrial 4.0 in Thailand - Chinachoti, Pavin (Asian Administration and Management Review, 2019)
The objectives of this research are; 1) to study the readiness of the industrial business sector towards the 4.0 industry in Thailand, and 2) to propose the approaches for the preparation of human resources of the industrial business sector towards the 4.0 industry in Thailand. This is qualitative research conducted by the in-depth interview. The informants consist of 1 industry council member, 5 members of each innovation-driven industrial group or the executives of industrial business in each industrial group, and 1 academician. The data used in the study is collected from the primary data which is the interview and the secondary data which is relevant documents and researches in order to obtain the issues of preparation of human resource management of the industrial business sector towards the 4.0 industry. The research results reveal that 1) the groups of industrial business sector towards the 4.0 industry in Thailand are ready to change and are in the operating process; for example, the organization's strategy to support changes in all aspects following the 4.0 industry’s driving strategies of the Federation of Thai Industries, the adoption of advanced technology and information technology to the production and marketing process, 2) the approaches in preparing for the readiness in human resources in terms of human resource planning requires the reduction in the number of human resources, and the selection of the organizations which focus on other options such as outsourcing, independent occupations, job rotation, etc. The required employee’s capacity is the ability to manage, diversity in working, speed in working, English proficiency, management of technology and information systems, cultivation of positive attitude to work, human resource development which is the training in the organizations, elearning, and the maintenance which is to set the salary base higher than the market, awards to increase the efficiency and innovation causing the employees to have fun in working, balance between work and personal life, family-style management that the executives in the industrial groups can apply the results to plan and prepare for human resource management.